Effects on collective behaviour and locomotor and neuromuscular response in young players by varying the length of the pitch in 11-a-side football - Nieto, S.; Castellano, J.; Echeazarra, I.; Fernández, E. (International Journal of Sports Science & Coaching, 2023)
The aim of this study was to describe the effects on collective behaviour and the physical response of young elite football players (Under 15) in the same 11 versus 11 task in three different pitch lengths (100, 75 and 50 m, LSG100, LSG75 and LSG50, respectively), keeping the width constant (60 m). The intra-team variables were: convex hull (CH), stretch index (SI), width (W), length (L) and length/width (L/W). The inter-team variables were calculated by using the 20 outfield players: CH2, W2, L2, L/W2 and DC (distance between centroids). The physical variables were: maximum speed (Vmax), number of accelerations (Acc) and decelerations (Dec) and total distance (TD). The results showed small (LSG100 > LSG75) and moderate-long differences (LSG100 > LSG50) for CH, SI and L. There was a moderate increase in DC and W2 (LSG50 > LSG75) and a moderate decrease in SI2, CH2, SI, L and CH (LSG75 > LSG50). The entropy was higher in SSG50 > LSG75 > LSG100. On a conditional level, the values showed differences between the three formats studied, showing more similarities between LSG50 and LSG100 than with LSG75. The main conclusion of the study was that the variation in the dimensions of the pitch caused a non-linear variation in the behavioural and conditional response in teams and players.